Nitrogen Fixation Responses in Sphagnum fuscum to N-Additions to an Alberta Peatland, 2012-2015 - R Kelman Wieder; Dale H Vitt; Melanie A Vile; Jeremy A Graham; Jeremy A Hartsock; Hope Fillingim; Melissa House; James C Quinn; Kimberli D Scott; Meaghan Petix; Kelly J McMillen (Environmental Data Initiative, 2019)
Development of the oil sands has led to increasing atmospheric N deposition, with values as high as 17 kg N ha -1 yr -1 ; regional background levels <2 kg N ha -1 yr -1 . Bogs, being ombrotrophic, may be especially susceptible to increasing N deposition. To examine responses to N deposition, over five years, we experimentally applied N (as NH 4 NO 3 ) to a bog near Mariana Lakes, Alberta, at rates of 0, 5, 10, 15, 20, and 25 kg N ha -1 yr -1 , plus controls (no water or N addition). We measured N 2 -fixation using the acetylene reduction technique between 2012 and 2015. All measurements were made between June and August. Mean acetylene reduction rates ranged from 2.2 mg m -2 da -1 (late June 2012) to 12.3 mg m -2 da -1 (late July 2014). Averaged across all measurement dates, rates were highest in the 5 kg N ha -1 yr -1 treatment, and decreased with increasing N loading. The acetylene reduction/N2 fixation response to N addition was described by a segmented linear regression, with rates increasing as N addition increased to 3.1 ± 1.5 kg N ha -1 yr -1 and decreasing with further increases in N addition. Water addition alone had no significant effect on N fixation rates on any of the measurement dates (p >= 0.79). While increasing N deposition may not substantively change total inputs of new N to bogs, the form on new N inputs shifts to inorganic N in deposition, rather than organic N produced by the microorganisms that are fixing N 2 .